African words and calques in Capeverdean Creole (Santiago variety) - (:unkn) unknown (My University, 2012)
Capeverdean (CV) is the mother tongue of more than a million people living in, ororiginating from, the archipelago of Cape Verde, situated about 500 km west of Dakar(Senegal). As a Portuguese-based Creole, this language obviously has many Portuguesederiveditems in its vocabulary, although there are often significant phonetic changes (see Quint 2000a: 53-139) such as:CV obi ‘to hear’ < Port. ouvir CV nabidja ‘heifer’ < Port. novilha.Nevertheless, not all CV words derive from Portuguese; indeed, some quite common CVwords can be traced back to diverse African languages, e.g.CV djobi ‘to look at’ < Mandinka juubee.CV djáki ‘bull calf’ < Wolof yëkk.In this article, I examine the importance of this African stratum and explore what Africanwords and expressions in CV can tell us about the origins of this language and, moregenerally, about the formation of Afro-European creoles.
Keywords: African Research